Edukasi Dan Sosialisasi Pentingnya Adaptasi Teknologi AI Dalam Pembelajaran - Munaldi; Yono Cahyono; Ahmad Arifin (CV. Multi Kreasi Media, 2026)
The development of information technology, particularly Artificial Intelligence (AI), has significantly influenced various aspects of life, including education. Although its use continues to generate debate among academics, AI has considerable potential to improve the efficiency and effectiveness of learning. This community service activity aimed to provide education and raise awareness regarding the importance of adapting AI technology in learning. The activity focused on introducing the basic concepts, benefits, and appropriate and responsible use of various AI-based tools. This technology can help educators access learning resources more easily, present interactive materials, provide feedback, and analyze students’ needs to support more personalized learning. The availability of mobile devices also enables broader and more flexible access to AI technology. This educational and awareness-raising activity was expected to enhance participants’ understanding, readiness, and awareness in utilizing AI as a learning support tool. Therefore, the responsible adaptation of AI technology can contribute to improving student engagement and the overall quality of the learning process and outcomes.